Quality of vision and outcomes after bilateral implantation of pseudo-non diffracting beam IOL - Pedrotti, Emilio; Bonacci, Erika; Kilian, Raphael; Pagnacco, Camilla; Anastasi, Marco; Ventura, Mariacarmela; Marchini, Giorgio (Frontiers in Medicine, 2023)
Purpose: To analyze the objective and subjective visual performances of a new hybrid refractive/aspheric extended depth of focus (EDOF) intraocular lens (IOL). Methods: In this monocentric prospective study patients with bilateral cataracts underwent cataract surgery and were implanted with a Lucidis IOL (SAV-IOL SA, Neuchâtel, Switzerland) in both eyes, one week apart from each other. At 3 months from implantation postoperative evaluations included monocular and binocular uncorrected and distance-corrected distant (4m), intermediate (80cm, 67cm) and near (40cm) visual acuities (UDVA/DCVA, UI80-67VA/ DCI80-67VA, UNVA/DCNVA), binocular defocus curves, halometry, contrast sensitivity and objective quality-of-vision measurements. Also, patients were also asked to complete the national eye institute refractive error quality of life (NEI-RQL-42) questionnaire. Results: Twenty-five patients (50 eyes) were included. The mean postoperative binocular UDVA, UI80VA, UI67VA and UNVA were -0.02±0.13, 0.05±0.09, 0.05±0.08 and 0.03±0.1 LogMar, and did not significantly differ from their corrected counterparts. On binocular defocus curves a VA 0.05LogMar was found between +0.50 and -2.50 D of vergence, whereas the mean distance from the central stimulus on halometry was 1.23±0.01. Mean ocular and corneal radical mean square at 4mm were 0.31±0.28 and 0.19±0.07, respectively; whereas the mean Strehl ratio was 0.2±0.09. Conclusions: Lucidis IOLs demonstrated excellent visual performances, especially at close distances while maintain good quality of vision, contrast sensitivity and overall patient-satisfaction.